The power of community how phenomenal leaders inspire their teams, wow their customers, and make bigger profits - Partridge, Howard (McGraw-Hill Education, 2018)
Business leaders often tell their people, Were all in this together, but very few follow through on this sentiment. Separate yourself from the pack by implementing the simple but profoundly effective methods in this book. --
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Corporate culture; Communities; Organizational behavior; Organizational Culture; Culture organisationnelle; Communauté; Comportement organisationnel